A critical review of abiotic and microbially-mediated chemical reduction rates of Fe(III) (oxyhydr)oxides using a reactivity model. (March 2021) - Xiu, Wei; Yuan, Wenjie; Polya, David A.; Guo, Huaming; Lloyd, Jonathan R.
Abstract: The reactivity of Fe (oxyhydr)oxides in reducing surface and sub-surface environments is a key factor controlling contaminant (e.g., As, U, Cr) solubility in natural waters and is also coupled tightly to multiple biogeochemical cycles (e.g., Fe, C, S, and P). The reactivity model ( J/m 0 = k'(m/m 0 ) γ ) has been extensively applied to predict the reduction kinetics of synthetic minerals and natural sediments. This critical review has compiled abiotic (155 experiments) and biotic (162 experiments) Fe(III) reduction in the presence or absence of added organic matter to quantify the apparent reaction order ( γ value) and apparent reaction rate constant ( k' ) of both natural and synthetic Fe(III) (oxyhydr)oxides. We found that both natural and synthesized Fe(III) (oxyhydr)oxides presented a range of γ and k' values towards biotic Fe(III) reduction, indicating that the heterogeneity in Fe(III) (oxyhydr)oxides are critical in providing a proxy for abiotic Fe(III) reduction kinetics. While considerable errors may arise when the abiotic γ and k' values of synthesized Fe(III) (oxyhydr)oxides are used to represent the γ and k' values of natural Fe(III) (oxyhydr)oxides where microbes are present. Similar microbially mediated median γ and k' values of natural and synthesized Fe(III) (oxyhydr)oxides highlight that microbial parameters significantly control the microbial Fe(III) reduction kinetics in addition to the heterogeneity in Fe(III) (oxyhydr)oxides (including the impurities and secondary Fe(III/II) mineralization, etc.), emphasizing the importance of microbial reactivities in better modelling the multiple biogeochemical cycle of Fe(III) (oxyhydr)oxides as well as the fate of contaminants solubility in global terrestrial and aquatic ecosystems. Graphical abstract: Image 1 Highlights: Fe(III) (oxyhydr)oxides presented various biotic and abiotic apparent reaction orders. Heterogeneity significantly controlled abiotic γ value of Fe(III) (oxyhydr)oxides. Microbial parameters critically affect biotic γ values of Fe(III) (oxyhydr)oxides.